Profil Keterampilan Berpikir Kritis Peserta Didik SMA pada Materi Suhu dan Kalor Melalui Tes Kontekstual - Putri Maharani Pertiwi; Oka Saputra; Imam Sya’roni; Hanandita Veda Saphira (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze the profile of high school students’ critical thinking skills on temperature and heat topics through contextual tests integrating real-life phenomena into scientific reasoning. This research employed a quantitative descriptive approach involving 36 twelfth-grade students at SMA Negeri 9 Surabaya. Data were collected using critical thinking tests based on Ennis’s five indicators, supported by non-test questionnaires and teacher interviews. The findings revealed that students’ critical thinking skills were still categorized as low, with indicator achievement ranging from 46.4% to 59.0%. The inference indicator obtained the lowest score, while strategy and tactics showed the highest score. The novelty of this study lies in the in-depth analysis of each Ennis critical thinking indicator specifically applied to temperature and heat materials in real-world contexts. These findings highlight the need for developing contextual interactive learning media to stimulate higher-order thinking skills and improve students’ critical thinking abilities.